Employing artificial intelligence in teaching arabic to non-native speakers, an analytical study on undergraduate students at Sultan Idris University in Malaysia - Duolingo application as a model - Usof, Abduloh; Mohd Zakaria, Zarima; Fiqiyah, Maskanatul; Issa, Koussoube; Samae, Abdulhalim (Arabic Translators International, 2025)
Artificial Intelligence (AI) is one of the most significant modern developments that has swept across the world. Many experts and stakeholders have attempted to integrate AI into their respective fields, such as engineering, medicine, arts, and various other domains. AI has also been utilized in the field of teaching English and other Latin-based languages. However, what is the role of AI in the learning and teaching of the Arabic language? Have educators succeeded in using AI to teach Arabic to non-native speakers? What challenges do teachers and learners face when employing AI in the teaching of Arabic to non-native speakers? To answer these questions, this research aims to evaluate the effectiveness of intelligent learning applications in teaching Arabic to non-native speakers. The study selected the Duolingo application as a model, with a sample of seventy undergraduate students from the Arabic Language Department at Sultan Idris Education University in Malaysia. The research employed both descriptive and analytical methods, where the researchers distributed a questionnaire to the students, gathered their responses, analyzed them, and derived the results of the study. The research is divided into an introduction and two main sections as follows: The first section: Theoretical framework, which includes a definition of AI, an overview of the Duolingo application, and its advantages and disadvantages. The second section: Practical framework, which examines the effectiveness of this application in the process of teaching Arabic to non-native speakers, the challenges students face while using the application, and appropriate solutions to these challenges. The study yielded several key findings, including that one of the main challenges students face when using the Duolingo application is the difficulty of remembering vocabulary. Therefore, Arabic language teachers need to develop suitable methods to help students memorize and recall vocabulary with ease. Additionally, the study found that intelligent applications are effective in helping students develop their language skills by enabling them to acquire new vocabulary and structures, as well as learn how to pronounce words correctly.